University-life balance: znaczenie infrastruktury uniwersyteckiej dla utrzymywania rezonansu ze światem i życiem prywatnym - Rogowski, Łukasz (Człowiek i Społeczeństwo, 2025)
The paper presents selected themes concerning the concept of university-life balance and its relevance to students’ lives. Based on Hartmut Rosa’s theory and the idea of work-life balance, selected dilemmas of students related to the requirement to combine activities in many spheres of life are indicated. These dilemmas are related to qualitative empirical research on the role of university infrastructure. The findings highlight the complexity of the relationship between university life and the private sphere of students and the multi-faceted role of infrastructure in this regard. Factors that create a positive resonance with the world are identified, including: flexibility, multi-sensoriality and safe infrastructure.